Alterações comportamentais durante a infecção experimental pelo Trypanosoma cruzi - Pereira, Glaucia Vilar (2011)
Since the discovery of Chagas disease in 1909, it is known that the protozoan parasite Trypanosoma cruzi infects the central nervous system (CNS). Neuropathological lesions with parasites in glial cells and, rarely, in CNS neurons are found during the acute phase of infection in humans. Even though neurological alterations are rare in the chronic phase, they seem to be severe in immunocompromised individuals such as those co-infected with human immunodeficiency virus (HIV), transplant or suffering from cancer. Behavioral changes, for instance depression, are detected in patients during chronic T. cruzi infection, but the cause of these disorders is unknown. Experimentally, C3H/He mice develop acute meningoencephalitis that is resolved in the chronic phase, while C57/BL6 mice are resistant to acute meningoencephalitis. However, T. cruzi and its antigens are found in the CNS of mice of both strains in the acute and chronic phases of infection. In this work, we propose to assess whether cognitive (memory/learning), motor and psychological (depression) changes are developed in experimental T. cruzi infection and test the hypothesis that, if present, behavioral alterations are consequences of acute meningoencephalitis. We used C3H/He and C57BL/6 mice strains, respectively, susceptible and resistant to T. cruzi-elicited acute meningoencephalitis. After intraperitoneal infection with 100 blood trypomastigotes of the Colombian T. cruzi strain, the animals were evaluated during the acute (30 dpi) and chronic (90 dpi) phases. The open field test was applied to evaluate locomotor and exploratory activities. Memory was assessed adopting object recognition and passive avoidance tests. The forced swim test and tail suspension were used to assess depression. The results of open field test showed neither exploratory nor motor abnormalities in animals susceptible or resistant to acute meningoencephalitis, during the acute and chronic phases of infection. The results obtained by means of the passive avoidance test suggest that T. cruzi infection does not interfere with aversive conditioning. However, T. cruzi infection of animals of C3H/He and C57BL/6 mice led to significant (p <0.05) alterations in memory recognition pattern, suggesting a mnemonic deficit during T. cruzi infection. Increased immobility time (p <0.0001), assessed by forced swim and tail suspension tests, was observed in infected mice of both C3H/He and C57BL/6 strains, being more expressive in animals of the C3H/He strain. Treatment with the antidepressive fluoxetine revealed improvement in depressive profile detected in infected mice of both strains, reinforcing the existence of behavioral disorders of neurological origin. In conclusion, we suggest that the behavioral changes (memory and learning disabilities as well as depression) are present during experimental T. cruzi infection, independently of the presence of acute meningoencephalitis, therefore not being its consequence